Health Education as a Strategic Approach to Prevent Acute Respiratory Infections (ARI): Health Education Strategy for ARI Prevention - Yuyun Tuasikal; Harianti Fajar (Journal of Evidence-Based Community Health, 2025)
Acute Respiratory Infections (ARI) remain one of the most prevalent diseases in the work area of the Laimu Care Community Health Center. Many people tend to ignore early symptoms, contributing to the increased risk of transmission. Therefore, an effective health education strategy is essential to raise public awareness and promote preventive behaviors. This activity aimed to improve public knowledge and preventive behaviors related to ARI through structured health education in the Laimu Health Center area. The health education strategy was implemented with 20 respondents during working hours at the health center. Preparations included the development of educational media (leaflets), coordination with health center staff, and approval for activity implementation. The educational session consisted of lectures, interactive discussions, and Q&A on ARI symptoms, transmission, and prevention. The findings showed that respondents’ knowledge about ARI was generally good. Out of 10 questions, most participants answered correctly on nine items, with only one item (related to transmission sources) showing a lower correct response rate. The education program also reinforced the importance of clean and healthy lifestyle habits. According to health center data, ARI ranks third among the top ten diseases in the area. Health education through lectures and printed media has proven effective in improving public knowledge and awareness of ARI. Continued health promotion is recommended to further reduce the incidence and risk of ARI transmission within the community